The Post-Growth Project : How the End of Economic Growth Could Bring a Fairer and Happier Society. - Blewitt, John (London Publishing Partnership, 2014)
This book challenges the assumption that it is bad news when the economy doesn't grow. For decades, it has been widely recognized that there are ecological limits to continuing economic growth and that different ways of living, working and organizing our economies are urgently required. This urgency has increased since the financial crash of 2007-2008, but mainstream economists and politicians are unable to think differently. The authors of this book demonstrate why our economic system demands ecologically unsustainable growth and the pursuit of more 'stuff'. They believe that what matters is.